"A State in the disguise of a Merchant": Tech Leviathans and the rule of law. Issue 1 (23rd September 2021) - D'Cunha, Christian
Abstract: The rule of law is a check on power, requiring equal subjection of everyone to the law, irrespective of wealth or status. Power is not the exclusive preserve of the state, however, especially where rivalled by private entities that rise, in effect, above the law. Today's tech giants throw the rule of law out of kilter by assuming the trappings of the state— one even has its own "supreme court"— while shunning its accountability. They seek to dissuade, capture and evade any attempt by the state to mitigate the harms arising from their business models. Policy makers scrambling for innovative legislative techniques are unlikely to repair the consequences of extreme concentration of corporate power so long as underlying social injustices and over‐deference in democratic institutions go unchallenged. Leviathan, whether in the form of govern mentor corporation, cannot coexist with the rule of law.